Optimalisasi Hasil Belajar Menggunakan Metode Cooperative Learning pada Materi Fiqih Bab Shalat di Minu 18 Lebak - Iltiqaul Jannah; Izul Herman (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Cooperative learning is an innovative, learner-focused teaching approach designed to enhance student participation and collaboration skills. This learning model divides students into small groups of 4-6 members, allowing them to collaborate actively. In these groups, students are encouraged to discuss, exchange ideas, solve problems together, and carry out their individual roles and responsibilities in order to achieve the overall goals of the group. This method primarily aims to develop students' social and academic skills through structured interaction and collaboration. In the cooperative learning model, students are divided into carefully designed small groups. Although the teacher provides basic materials and guidance, the main focus is on the interaction between group members. Each member has an important role in the learning process, where they are not only responsible for understanding the material themselves, but also helping and supporting other group members in achieving understanding. In implementing the use of cooperative learning to optimize learning outcomes in the fiqh material on the chapter on prayer, the preparation made by the teacher is to determine the material in the chapter on prayer (for example, obligatory prayer, conditions and pillars of prayer, prayer readings and congregational prayer). Prepare media (video tutorials, worksheets, pictures of the pillars of prayer).